The future of fruit and vegetables in Benin’s food system: visioning alternative scenarios toward 2060 - Mitchodigni-Houndoloa, Irene Medeme; Iruhiriye, Elyse; Egahc, Janvier; Afed, Ogouyôm Herbert Iko; Madoded, Yann Emeric; Ayenana, Mathieu A.T; Salaoue, Abdou Mouizz; Videglaf, Euloge; Schreinemachersg, Pepijn; Pitersh, Bart de Steenhuijsen (CGIAR, 2024)
Fruits and vegetables (F&V) share health benefits due to common phytochemicals (e.g., phenolics, flavonoids, carotenoids), vitamins (e.g., vitamin C, folate, pro-vitamin A), minerals (e.g., potassium, calcium, magnesium) and fibers (Kalmpourtzidou et al, 2020). According to World Health Organization (WHO) and Food and Agriculture Organization (FAO) guidelines (2003), the recommended consumption of fruits and vegetables is at least 400 g/day (WHO & FAO, 2003). Unfortunately, F&V intake is far below this recommendation, and the situation is alarming, especially in low- and middle-income countries (LMICs) (CGIAR, 2021). Poor diets are a primary cause of malnutrition and the leading cause of non-communicable disease (NCD) worldwide. Improving diets, including F&V intake, could save one in five lives annually. However, the extent and nature of the problem are poorly understood due to insufficient dietary data, particularly in LMICs. Increasing F&V intake will require starting with consumers, understanding dietary patterns, and addressing desirability, accessibility, affordability, and availability barriers through cost-effective solutions using the end-to-end approach. Solutions to the intractable problem of low F&V intake must be multifaceted and interconnected, requiring a holistic end-to-end approach such as the approach undertaken by the FRESH Initiative. This report describes the results of expert and stakeholder consultations held from 4 to 8 March 2024, organized by the CGIAR Research Initiative on Fruit and Vegetables for Sustainable Healthy Diets (FRESH). The exercise aimed to explore the future role of fruits and vegetables in Benin's food system. These crops are critically important to healthy diets and generate income to value chain actors. It is, therefore, important to understand which trends and uncertainties may shape the future food system and what actors can do to steer developments in the desired direction. In this report, the approach to such foresight analysis is explained, as well as the current state of fruits and vegetables in Benin's food system. Alternative futures are explored regarding their consequences and options for anticipatory policy and stakeholder engagement.